2018
DOI: 10.1088/1748-9326/aabc61
|View full text |Cite
|
Sign up to set email alerts
|

The importance of forest structure for carbon fluxes of the Amazon rainforest

Abstract: Precise descriptions of forest productivity, biomass, and structure are essential for understanding ecosystem responses to climatic and anthropogenic changes. However, relations between these components are complex, in particular for tropical forests.We developed an approach to simulate carbon dynamics in the Amazon rainforest including around 410 billion individual trees within 7.8 million km 2 . We integrated canopy height observations from space-borne LIDAR in order to quantify spatial variations in forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
80
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 51 publications
6
80
0
4
Order By: Relevance
“…The tropical evergreen forest of Amazonia holds 34% of terrestrial carbon stocks and makes up a significant fraction of the global carbon sink (Beer et al, 2010;Pan et al, 2011;Rödig et al, 2018). Improved model representation of the region's carbon and water fluxes is important if we are to assess their ongoing and future changes (Fu et al, 2013;Peñuelas & Filella, 2009;Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The tropical evergreen forest of Amazonia holds 34% of terrestrial carbon stocks and makes up a significant fraction of the global carbon sink (Beer et al, 2010;Pan et al, 2011;Rödig et al, 2018). Improved model representation of the region's carbon and water fluxes is important if we are to assess their ongoing and future changes (Fu et al, 2013;Peñuelas & Filella, 2009;Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In most existing LSMs, a strong positive linear relation between NPP and AGB emerges in the forest of the Amazon basin that is not observed in the inventory plots (Johnson et al 2016). Rödig et al (2018) show that when successional stages and individual tree mortality from, for example self-thinning, are incorporated, the model is able to simulate a bell-shaped relation between ANPP and AGB with an optimum of potential ANPP at an AGB of 250 Mg C ha −1 , similar to what is observed in inventory plots.…”
mentioning
confidence: 96%
“…Furthermore, other mechanisms that influence tree growth and survival such as soil phosphorus acquisition, storm damage, droughts, fires and deforestation, all deserve a place in future LSMs but have also proven to be notoriously difficult to incorporate into predictive models. This is the point where Rödig et al (2018) enter the stage. The authors incorporated a LIDAR derived canopy height map of the entire Amazon basin into a numerical model that simulates individual tree growth.…”
mentioning
confidence: 99%
“…Recent efforts aiming at improving simulated Amazon forest biomass and productivity by including spatial variation in biophysical parameters (such as τ and Vcmax) have found that using single values for key parameters limits simulation 15 accuracy (Castanho et al, 2013). Thus, we conclude that a more mechanistic representation of the processes driving the spatial variability of carbon stocks and fluxes, forest structure and tree demographic dynamics is necessary to improve simulation accuracy (Rödig et al, 2018).…”
Section: What Can We Learn From Including Spatial Heterogeneity and Umentioning
confidence: 87%